Workplace spirituality and organizational commitment influence on job performance among Academic Staff - Campbell, James Kennedy; Yen, Siew Hwa (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study examines the relationships between spirituality in the workplace, organizational commitment and job performance measured in terms of key performance indicators (KPIs) based on a sample of 376 academic staff at Universiti Sains Malaysia (USM). The methods used in the study are factor analysis and multiple regression analysis. Three factors are found to explain organizational commitment: affective commitment, continuance commitment and normative commitment. Affective and normative commitments are positively influenced by workplace spirituality, which is explained by three factors: alignment between organizational and individual values; sense of enjoyment at work and contribution to community; and opportunity for inner life. The study also finds that neither high commitment nor workplace spirituality among academic staff necessarily manifest in high KPIs. Instead, other staff background variables appear to have more influence on job performance, such as gender, stream, age and rank.